Cosmopolitan cultures and oceanic thought
1 online resource (x, 270 pages)
Keywords: "This book imagines the ocean as central to understanding the world and its connections in history, literature and the social sciences. Introducing the central conceptual category of ocean as method, it analyzes the histories of movement and traversing across connected spaces of water and land sedimented in literary texts, folklore, local histories, autobiographies, music and performance. It explores the constant flow of people, material and ideologies across the waters and how they make their presence felt in a cosmopolitan thinking of the connections of the world. Going beyond violent histories of slavery and indenture that generate global connections, it tracks the movements of sailors, boatmen, religious teachers, merchants, and adventurers. The essays in this volume summon up this miscegenated history in which land and water are ever linked. A significant rethinking of world history, this volume will be of great interest to scholars and researchers of history, especially connected history and maritime history, literature, and Global South studies"--